Contralateral effects of eccentric resistance training on immobilized arm. (22nd September 2020) - Valdes, Omar; Ramirez, Carlos; Perez, Felipe; Garcia‐Vicencio, Sebastian; Nosaka, Kazunori; Penailillo, Luis
Abstract: This study compared the effects of contralateral eccentric‐only (ECC) and concentric‐/eccentric‐coupled resistance training (CON‐ECC) of the elbow flexors on immobilized arm. Thirty healthy participants (18‐34 y) were randomly allocated to immobilization only (CTRL; n = 10), immobilization and ECC (n = 10), or immobilization and CON‐ECC group (n = 10). The non‐dominant arms of all participants were immobilized (8 h·day −1 ) for 4 weeks, during which ECC and CON‐ECC were performed by the dominant (non‐immobilized) arm 3 times a week (3‐6 sets of 10 repetitions per session) with an 80%‐120% and 60%‐90% of one concentric repetition maximum (1‐RM) load, respectively, matching the total training volume. Arm circumference, 1‐RM and maximal voluntary isometric contraction (MVIC) strength, biceps brachii surface electromyogram amplitude (sEMGRMS ), rate of force development (RFD), and joint position sense (JPS) were measured for both arms before and after immobilization. CTRL showed decreases ( P < .05) in MVIC (−21.7%), sEMGRMS (−35.2%), RFD (−26.0%), 1‐RM (−14.4%), JPS (−87.4%), and arm circumference (−5.1%) of the immobilized arm. These deficits were attenuated or eliminated by ECC and CON‐ECC, with greater effect sizes for ECC than CON‐ECC in MVIC (0.29: +12.1%, vs −0.18: −0.1%) and sEMGRMS (0.31:17.5% vs −0.15: −5.9%). For the trained arm, ECC showed greater effect size for MVIC than CON‐ECC (0.47 vs 0.29), and increased arm circumference (+2.9%), sEMGRMS (+77.9%), and RDF (+31.8%) greater ( P < .05) than CON‐ECC (+0.6%, +15.1%, and + 15.8%, respectively). The eccentric‐only resistance training of the contralateral arm was more effective to counteract the negative immobilization effects than the concentric‐eccentric training.